INTEGRAL EDUCATION: SUBJECTIVE PUBLIC RIGHT - Pedro Ganzeli (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
The idea of integral education involves multiple possibilities of comprehension, particularly in policies, programs, projects, among other aspects of the organization of educational space, related to the expansion of the time that students spent in educational activities, which in turn, serve a particular state model. This article aims to analyze the idea of integral education from the perspective of the formation of the subject of law. Initially we present the model of the social state of law as prescribed in the Constitution of the Federative Republic of Brazil, in October 1988, as a reference to the definition of the three constituent premises of integral education: full development of the person, preparation for the exercise of citizenship and qualification for work. After that, explore the basic features of participatory planning, which is essential for the conduct of integral education in educational spaces. Considering that education in the perspective of the formation of the subject of law, must meet the integrality of the human being, this study contributes to the construction of conceptual framework of the integral education. Keywords: Integral Education. Participatory Planning. Social State of Law.